2014
DOI: 10.4103/0973-1482.151482
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and colorectal neoplasm risk: A meta-analysis Based on East Asian population

Abstract: In general, no statistical association between HP infection and colorectal neoplasm risk was found in this meta-analysis. But, HP infection may increase the risk of developing colorectal adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 16 publications
1
24
2
Order By: Relevance
“…These differences in population characteristics may explain, at least in part, the discrepancies between our results and those of Epplein et al . Previous studies support the idea of differences by study population in the association between H. pylori and colorectal cancer as well as precursors such as polyps and adenomas .…”
Section: Discussioncontrasting
confidence: 64%
“…These differences in population characteristics may explain, at least in part, the discrepancies between our results and those of Epplein et al . Previous studies support the idea of differences by study population in the association between H. pylori and colorectal cancer as well as precursors such as polyps and adenomas .…”
Section: Discussioncontrasting
confidence: 64%
“…Abbreviation: HP, Helicobacter pylori; Hx, history disagree. 12,13,26,27 The reason for this discrepancy is currently uncertain, but our results suggest that age is an important factor that determines the association between H. pylori and ACN. In line with our results, studies by Limburg et al, 28 Chen et al, 12 and Blase et al, 13 suggesting that H. pylori did not increase the level of gastrin in the elderly.…”
Section: Discussionmentioning
confidence: 73%
“…21 In this study, Lee et al Previous studies, however, showed that the observed relationship between H. pylori and CRC could be population related. 23,24 In a nested case-control study on an elderly, mainly Caucasian population (392 cases, 774 controls, age: 56-87 years, median age when blood was drawn: 71 years), the association between H. pylori seropositivity, defined as reactivity to at least 4 of 15 analyzed proteins, and CRC was evaluated. Overall H. pylori seropositivity was not related to a higher CRC risk.…”
Section: H Pylori and Colorectal Cancermentioning
confidence: 99%